Faktor-Faktor yang Mempengaruhi Integritas Laporan Keuangan pada Perusahaan Manufaktur - Susanto Salim, Sella Destika, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
This study aims to empirically examine the effect of financial distress, leverage, profitability, and firm size on accounting conservatism principles in manufacturing companies in Indonesia. The sample used in this study was selected using the purposive sampling method and 90 manufacturing companies listed on the IDX were selected during the period 2017 to 2019 with a total of 250 observations. This research was conducted using multiple regression analysis with Random Effect Model (REM) as the regression model. The data in this study were processed using the Econometric Views (EViews) software version 12. The results of the study found that financial distress, leverage, profitability, and firm size affect accounting conservatism. More specifically, financial distress and firm size have a non-significant positive effect on accounting conservatism, while leverage and profitability have a significant negative effect on accounting conservatism.